Predicting distant metastasis and chemotherapy benefit in locally advanced rectal cancer - Zhenyu Liu (Nature Portfolio, 2020)
Distant metastasis (DM) is the main cause of treatment failure in locally advanced rectal cancer. Here, the authors developed and validated a radiomic signature (RS) for prediction of DM within a multicenter dataset, and suggest that it may help with stratification of patients who might benefit from adjuvant chemotherapy for DM.